Productivity profile of CNPq scholarship researchers in Physical Education - Ludmila Cotrim Fagundes; Carolina Júnia Reis Paz; Daniel Antunes Freitas; Wellington Danilo Soares (Universidade Estadual Paulista (UNESP), 2020)
Abstract To categorize the profile of scientific productivity scholarship researchers of the National Council for Scientific and Technological Development (CNPq) in the area of Physical Education. This is a quantitative, cross-sectional, descriptive and correlational study, whose participants were researchers in Physical Education scholarship holders of research productivity from CNPq, between 2015 and 2019, evaluated from the lists of productivity scholarships in force at CNPq. Results were categorized for statistical analysis. We found 92 current research productivity grants. Of these, 75% are destined for men, 58.7% fall into the PQ-2 category and most are concentrated in the Southeast region. More than 50% of productivity scholarship counselors do not mentor any postdoctoral students, but rather advise between 1 and 3 doctoral and master's students. 22.2% of the Midwestern scholarship holders published more than 100 articles and in the Southeast, there are the largest producers of books and book chapters, and about 6% of scholarship holders in this region had more than 20 publications. It can be inferred that there was a higher concentration of Physical Education researchers in the southeast region, with a higher prevalence for males, concentrating the majority of scholarship holders in the PQ-2 area. Through the identification of the profile of the fellows in the Physical Education area, more effective criteria and forms can be better established in order to stimulate scientific production, as well as the demands for the promotion of new research proposals.